The incidence of human capital on economic inequality in Latin America - Medina Flores, Michael Antonio; Burgos Zavaleta, Victor Fernando Jesus (mktDESCUBRE; Vol 1 No 24 (2024): Twenty-fourth Edition (July - December), 2024)
Objective : This article aims to evaluate the impact of human capital on economic inequality in the short and long term in fourteen Latin American countries during the period 2000-2019. Methodology: An ARDL panel econometric model was used to evaluate short- and long-term impacts. Results: The results obtained reveal a relationship between human capital and economic inequality in the 14 Latin American countries analyzed during the study period from 2000 to 2019. Conclusions: In the long term, a positive association was found and significant. However, in the short term, a negative relationship was found between human capital and inequality.